Proposed Algorithm For Encrypting the JEPG Compressed Image - رحمة، عبدالمنعم صالح; العابدي، زينب جواد حنش (كلية المنصور الجامعة, 2017)
In image encryption algorithms, encryption security and encryption speed are important aspects in the field of data transmission (includ¬ing digital image transmission) via the Internet, the need arises to protect data by encrypting it, in this paper proposes an algorithm that is characterized by precision and safety. It works in 15 rounds and applies encryption to the compressed image (JPEG), Taking into consideration data image of loss after the decryption process. The goal is to supply a highly secure encryption algorithm with increase the speed significantly based on field GF (P) that adopted in the algorithm advance encryption standard (AES).
في خوارزميات التشفير، الأمن والسرعة من الجوانب الهامة في مجال نقل البيانات (بما في ذلك نقل الصور الرقمية) عبر الإنترنيت، ولحماية البيانات يتم تشفيرها. في هذا البحث تم اقتراح خوارزمية تتميز بالدقة والأمان وتعمل على round (15) مع الأخذ بنظر الاعتبار الحفاظ على بيانات الصورة من الفقدان بعد عملية فك التشفير وتطبق على الصورة الرقمية (jpeg)وبالاعتماد على حقل GF(P)حيث حققت هذه الخوارزمية السرعة المطلوبة مع التعقيد، وذلك بالتعديل على خوارزمية. (AES)
Keywords: الخوارزميات -- الصور الرقمية -- نقل البيانات -- التشفير